1999
DOI: 10.1044/0161-1461.3002.183
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawn and Sociable Behavior of Children With Language Impairment

Abstract: This study examined the dimensions of withdrawal and sociability in children with language impairment (LI) and their typically developing chronological age-matched peers. Classroom teachers rated the withdrawn and sociable behaviors of 41 children with LI and 41 typically developing peers using the Teacher Behavioral Rating Scale (TBRS, Hart & Robinson, 1996). Children were sampled from the age ranges of 5 to 8 years and 10 to 13 years. Subtypes of both withdrawn (solitary-passive withdrawal, solitary-active w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 27 publications
5
112
0
3
Order By: Relevance
“…There are mixed findings in the literature with respect to the associations between prosocial behaviour and language ability with both younger and older samples of children (Barnett et al, 2012;Ensor & Hughes, 2005;Horwitz et al, 2003;Fujiki et al, 1999;Ketelaars et al, 2010;Rhee et al, 2013;Von Grunigen et al, 2012). The results of the current study are Prosocial Behaviour and Expressive Language 13 in line with previous studies that have found positive associations, direct and indirect, between language and prosocial behaviour in the early years of development (e.g., Ensor & Hughes, 2005;Rhee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are mixed findings in the literature with respect to the associations between prosocial behaviour and language ability with both younger and older samples of children (Barnett et al, 2012;Ensor & Hughes, 2005;Horwitz et al, 2003;Fujiki et al, 1999;Ketelaars et al, 2010;Rhee et al, 2013;Von Grunigen et al, 2012). The results of the current study are Prosocial Behaviour and Expressive Language 13 in line with previous studies that have found positive associations, direct and indirect, between language and prosocial behaviour in the early years of development (e.g., Ensor & Hughes, 2005;Rhee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2004;Horwitz et al, 2003;Fujiki et al, 1999;Ketelaars et al, 2010;von Grunigen, Kochenderfer-Ladd, Perren, & Alsakar, 2012). While this is an important area of investigation, it fails to address how associations between language and prosocial behaviour would present in typically developing children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por tanto, las oportunidades de estos sujetos para socializarse con sus iguales quedan restringidas por sus pobres aptitudes comunicativas, sobre las cuales no se interviene de forma sistemática, lo que puede llevar a que decrezca su participación social e incluso que sean rechazados por parte de sus iguales . Además, existe el peligro de que el desarrollo de su CS se vea retrasado (Fujiki, Brinton, Morgan, & Hart, 1999). Análogamente, las habilidades pragmáticas están altamente relacionadas con el desarrollo de una CS competente.…”
Section: El Caso Del Tplunclassified
“…Considering the findings of these two studies, perhaps the CNS involvement related to alcohol exposure can be manifested in a variety of ways, one of which is neuropsychological deficits with concomitant social problems. For children with language-learning problems or attention-deficit/hyperactivity disorder, studies suggest that their neurological impairments may contribute to problems in social interactions (Brinton & Fujiki, 1993;Bruce, Thernlund, & Nettelbladt, 2006;Fujiki, Brinton, Morgan, & Hart, 1999;Redmond & Rice, 1998). Children with FASD may share this characteristic.…”
Section: Classroom Performance From a Dimension Perspective: Childrenmentioning
confidence: 99%